Medico-legal considerations on "Lotus Birth" in the Italian legislative framework - Alessandro Bonsignore; Francesca Buffelli; Rosagemma Ciliberti; Francesco Ventura; Andrea Molinelli; Ezio Fulcheri (BMC, 2019)
Abstract The term "Lotus Birth" identifies the practice of not cutting the umbilical cord and of leaving the placenta attached to the newborn after its expulsion until it detaches spontaneously, which generally occurs 3-10 days after birth. The first reported cases of Lotus Birth date back to 2004 in Australia. Supporters of such a procedure claim that the newborn is better perfused, endowed with a more robust immune system and "less stressed". However, it should be pointed out that histopathological study of the placenta is increasingly being requested in order to investigate problems of an infective nature or dysmaturity affecting the foetus, and situations of risk affecting the mother. Moreover, from the legal standpoint, there is no uniform position on the question of whether the placenta belongs to the mother or to the newborn. Lastly, a proper conservation of the embryonic adnexa is very difficult and includes problems of a hygiene/health, infectivological and medico-legal nature. The authors analyzed all these aspect in the Italian legislative framework, reaching the conclusion that Lotus Birth is inadvisable from both the scientific and logical/rational points of view.